2019
DOI: 10.1088/1361-6501/ab019d
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive sampling methodology for measuring blades with CMM based on dominant feature points

Abstract: Sampling strategy is one of the most critical components of the contact probing process with coordinate measuring machines (CMMs). The number and location of sampling points have direct impacts on the efficiency and reliability of the measurements. Blades of aviation engines have complex geometry and extremely high precision requirements, but the sampling strategy of blades is still a difficult problem which limits the use of CMMs in blade inspection. To balance the measuring efficiency and accuracy of CMM, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Knot points are the most important and informative points and after simplification they indicate crucial shape changes. The original CAD section contains 104 smaller Bezier curves (Figure 7a), which is more than needed, as proved by other authors [15,[17][18][19][20][21][22][23][24][25][26]. It was rebuilt using knot removal methods and it was concluded that for CMM measurement the number of control points can be slightly decreased, reducing it to 20-30.…”
Section: Calculationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Knot points are the most important and informative points and after simplification they indicate crucial shape changes. The original CAD section contains 104 smaller Bezier curves (Figure 7a), which is more than needed, as proved by other authors [15,[17][18][19][20][21][22][23][24][25][26]. It was rebuilt using knot removal methods and it was concluded that for CMM measurement the number of control points can be slightly decreased, reducing it to 20-30.…”
Section: Calculationsmentioning
confidence: 87%
“…Yun Zhang [20] developed a sampling method for twisted blades to improve measurement efficiency. A very similar method was developed by Feiyan Guo [21] for a turbine guide vane. Xuezhe Li [22] focused his attention on the twist itself, to solve high-precision measurement problems with this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The special scanning pattern of five-axis sweep scanning requires the sampling path to be a sinusoidal curve [12]. The traditional sampling strategies in three-axis CMM inspection cannot fully manifest the dynamic performance of the five-axis sweep scanning [13][14][15][16]. Thus, a suitable sampling strategy for five-axis CMM inspection should be investigated.…”
Section: Motivationsmentioning
confidence: 99%
“…Guo et al proposed an adaptive detection algorithm based on an advantage feature point. The algorithm adaptively detects integral points by modifying the B-spline least-squares fitting process, determining the profile curve of the measured surface by this method and using the main feature points of the profile to determine points in the measuring area [20]. Zhao et al proposed a new detection method for free-form surface inspection and inspection points, by dividing the surface to be measured into several sections that make it easy to construct B-splines, and obtain the data points needed to construct B-splines as inspection points [21].…”
Section: Related Workmentioning
confidence: 99%
“…After that, the clustering center of each cluster Assume that {x i } N i=1 represents a sample set of size N. Based on the K-means method we divide the sample set into K clusters (K < N). The mapping is shown as equation (20), which divides the ith sample x i into k clusters:…”
Section: Calculation Of Weight Parametersmentioning
confidence: 99%